Assessing the current practices of solid waste management in Selangor urban area / Nur Ashikin Abdul Rashid - Abdul Rashid, Nur Ashikin (Faculty of Architecture , Planning and Surveying, 2015)
Nowadays, solid waste is one of the most current issues that had been talk by everyone. This situation will brought serious environmental issues and social threat if it does not solve. Recently, there are many alternatives method that used by the Local Authority in reducing the solid waste generation. This study being conducted in urban area those are around Selangor. This study was conducted because solid waste in urban area are increasing from year to year. Local authorities also had problems in upgrading the waste management in urban area. The aim of this research is at assessing the current practices of solid waste management (SWM) by the local authorities and the parties in urban area especially in Selangor area. This research are designed to achieve three main objectives that are (i) to identify the SWM in urban area; (ii) to examine the challenges of the SWM in urban area by the local authorities and other parties involved; (iii) to give recommendation on how to upgrading the SWM in Selangor urban area. To achieve these three main objectives, this research has been conducted by using secondary data from the online databases, books, online journal etc. and secondary data from the structured interviews through the local authorities and other parties involved and observations through site visit. The result from this research indicates that the main challenge in managing solid waste is the lack of awareness from the public.